Policy Implications and Cost of Prevention of Juvenile Delinquency: A Willingness Survey of College-Educated-Adults for Communities That Care - Samuel Arungwa; Gbolahan S. Osho (Journal of Sociological Research, 2024)
The juvenile crimes and problem behaviors discussed above tend to come to a head within the local communities where juvenile crimes are often committed. Gaining a community-level appreciation of juvenile crime is essential because national statistics often make readers feel that their neighborhood might be exempt. Drug abuse is undoubtedly a global issue. American experts have monitored and published critical drug prevention studies conducted in other continents and nations outside of the Americas for more than a decade. Thus, the main goal of this current research study is to provide insights into the cost of preventing juvenile delinquency through a willingness survey of college-educated adults for communities that care and proffer policy solutions. One such study is a co-twin controls study conducted in Australia (Lynskey et al., 2003). The study conclusions and recommendations are an essential foundation for future studies relating to this WITS4CTC perspective. While the tone in this study discussion may seem to imply that colleges have done little to support CTC, it remains impossible to know whether some have tried, however secretly, to support CTC outside the radar of CTC researchers and social scientists. Even more importantly, there may be some, amongst the thousands, who sincerely wish to help with CTC but lack a model that can remotely serve as a guide. If any such latent supportive CEAs and colleges exist already, then this work could not have come a moment too soon. Therefore, It is hoped that this would benefit many CEAs and CTC stakeholders.